2011
DOI: 10.1136/bmj.d5278
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caudal epidural steroid or saline injection in chronic lumbar radiculopathy: multicentre, blinded, randomised controlled trial

Abstract: Objective To assess the efficacy of caudal epidural steroid or saline injection in chronic lumbar radiculopathy in the short (6 weeks), intermediate (12 weeks), and long term (52 weeks).Design Multicentre, blinded, randomised controlled trial.Setting Outpatient multidisciplinary back clinics of five Norwegian hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
175
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(181 citation statements)
references
References 73 publications
2
175
0
4
Order By: Relevance
“…Three caudal injections of 20 ml bupivacaine 0.25% + 80 mg methylprednisolone. Iversen 67 RCT P DB 116 patients with lumbar radiculopathy >12 wk.…”
Section: Control Group Outcome Measures Results Commentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three caudal injections of 20 ml bupivacaine 0.25% + 80 mg methylprednisolone. Iversen 67 RCT P DB 116 patients with lumbar radiculopathy >12 wk.…”
Section: Control Group Outcome Measures Results Commentsmentioning
confidence: 99%
“…When global pain ratings were not available for aggregate analysis, leg pain ratings were used in their place. 37,52,[65][66][67][68][69] Baseline and comparison data were the most recent data points available before and after the first injection (or injection series), respectively. All comparison data were observed within 12 weeks of the initial injection (if the injection scheme was open-ended) or after the final injection in the first injection series.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A blinded randomized control trial by Iversen et al published in 2011 found CESI to not be effective in treating chronic (>12 weeks) lumbar radicular pain with their results showing no statistical or clinical difference between sham groups and groups who received CESI [128]. Their study was slightly underpowered.…”
Section: Efficacymentioning
confidence: 99%